The effectiveness of hippotherapy in relation to cerebral palsy - a review - Damian Bator; Magdalena Wójcik; Julita Szarpak; Hubert Nieścior; Justyna Dąbrowska; Halina Piecewicz-Szczęsna (Kazimierz Wielki University, 2020)
Cerebral Palsy (CP) includes a group of movement and posture development disorders which cause activity limitation and are related to non-progressive disturbances during the fetal or infant brain development. In recent years, the use of hippotherapy as a rehabilitation of spstatic movement disorders in patients with  cerebral palsy is gaining in popularity. Hippotherapy is a physical therapy treatment based on the horse's movements, under the direction of an expert physical therapist. The horse's seat is considered as a dynamic support base. Thus, it <span class="SpellingError SCXW53512727